Pericoronary fat radiomic profile (FRP) predicts long-term cardiac risk in individuals with calcium score below 100 on coronary computed tomography angiography. (25th November 2020) - Kotanidis, C.P; Oikonomou, E.K; Williams, M.C; Thomas, S; Thomas, K.E; Lyasheva, M; Antonopoulos, A.S; Dweck, M.R; Shirodaria, C; Neubauer, S; Channon, K.M; Newby, D.E; et al.
Abstract: Background: Coronary computed tomography angiography (CCTA) provides useful information regarding cardiovascular risk assessment. Key aspects of coronary biology induce changes in perivascular adipose tissue composition, detectable by the pericoronary Fat Radiomic Profile (FRP) index. Purpose: We assessed the ability of FRP to further stratify cardiac risk in patients with Coronary Artery Calcium (CAC) scoring below 100 following routine CCTA. Methods: The study population consisted of 1, 575 participants from the CCTA arm of the SCOT-HEART trial (NCT01149590) with images available and eligible for analysis. Pericoronary FRP mapping was performed in perivascular adipose tissue segmentations around the proximal sites of the right and left coronary arteries, as previously validated. The prognostic potential of FRP was initially tested in a sub-cohort, consisting of patients with Coronary Artery Calcium (CAC) score lower than 100. Further analysis was performed after sub-grouping based on the absence of high risk plaque (HRP) features and obstructive coronary artery disease (CAD). The association with future incidence of major adverse cardiac events (MACE: cardiac mortality or non-fatal myocardial infarction) or a composite endpoint of MACE ± late revascularization (MACE-ReVasc) was assessed using adjusted Cox regression models [adjusted for age, sex, systolic blood pressure (SBP), diabetes mellitus (DM), body mass index (BMI), smoking, CAD (≥50% stenosis), total cholesterol, high-density lipoprotein (HDL), and HRP features]. Results: Two-thirds (66%) of the study population were at low-risk according to the CAC score (CAC<100). Over a mean follow-up of 4.87±1.06 years, 12 MACE and 47 MACE-ReVasc were recorded. In this sub-cohort, high FRP was associated with a 14.4-fold (95% CI: 3.80–54.78, p<0.001) higher adjusted risk of MACE and a 2.8-fold (95% CI: 1.49–5.36, p=0.001) higher adjusted risk of MACE-ReVasc. Adding high FRP to a baseline model consisting of traditional risk factors (age, sex, systolic blood pressure, diabetes mellitus, BMI, smoking, CAD (≥50% stenosis), total cholesterol, HDL, HRP) significantly enhanced (deltaAUC at 5 years:0.15, p=0.03) the model's performance (A) and reclassified individuals (NRI=0.59, p=0.02). Interestingly, following further filtering of the population by the absence of HRP features and obstructive CAD, high FRP remained an independent predictor of MACE (B). Conclusion: The Fat Radiomic Profile biormarker significantly improves risk prediction for adverse clinical events beyond the current state-of-the-art in individuals with low CAC scores. Non-invasive profiling of pericoronary adipose tissue using CCTA-derived FRP captures irreversible changes in perivascular adipose tissue composition associated with chronic vascular inflammation and atherosclerotic disease, and can improve risk stratification and clinical decision making in low-risk populations. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): British Heart Foundation, National Institute of Health Research, Oxford Biomedical Research Centre